Empowering Entrepreneurial Teams through Shared Leadership: Insights from Indonesia's Entrepreneurship Programs - Andika; Radityo Putro Handrito; Ana Sofia Aryati (Jurnal Ilmiah Administrasi Publik, 2026)
This study examines the impact of shared leadership on entrepreneurial team performance. Based on Social Exchange Theory (SET), we investigate the role of shared leadership in enhancing team performance through team trust and team creativity as mediators. Data were collected from 71 entrepreneurial teams, consisting of 306 members and 73 supervisors, through a combined online and offline survey. Using Smart PLS 3.0, the aggregate data were analyzed at the team level within a mediation framework. The findings indicate that shared leadership significantly enhances team performance, with trust and creativity playing a partial mediating role. This study contributes to the literature by highlighting team creativity as a new mediator and utilizing dyadic data to reduce bias. The results of this study emphasize the importance of fostering trust and creativity to enhance team effectiveness, offering valuable implications for strengthening entrepreneurship programs in Indonesia and achieving sustainable success